A Short History of Christianity Beyond the West : Asia, Africa, and Latin America 1450-2000 - Koschorke, Klaus (Religious Studies, Theology and Philosophy E-Books Online, Collection 2025., 2024)
Today, the majority of the world's Christian population lives in the Global South. Knowledge of their history is therefore indispensable. This textbook offers a compact and vivid overview of the history of Christianity in Asia, Africa and Latin